Spatial indicator of priority areas for the implementation of agroforestry systems: An optimization strategy for agricultural landscapes restoration - de Mendonça, Gislaine Costa [UNESP]; Costa, Renata Cristina Araújo [UNESP]; Parras, Rafael [UNESP]; de Oliveira, Laís Caroline Marianno [UNESP]; Abdo, Maria Teresa Vilela Nogueira [UNESP]; Pacheco, Fernando António Leal [UNESP]; Pissarra, Teresa Cristina Tarlé [UNESP] (Elsevier, 2022)
The ecological functions restoration in agricultural areas is a major challenge on a landscape scale. In the specific case of active restoration through Agroforestry Systems (AFS), the absence of a specific direction hinders ecological restoration processes, especially in regions that prefer intensive agriculture. Thus, this study aims to develop a Spatial Indicator of Priority Areas to guide Agroforestry Systems implementation in agricultural landscapes. A spatial multicriteria decision analysis (MDCA) was carried out based on environmental factors: soil, geology and slope (which determine the natural vulnerability of the land) and anthropogenic factors: land use and land cover, forest fragments, potential land use capacity and legal protected areas in rural properties (which reflects human pressure and land use suitability). Subsequently, four priority levels were classified for agroforestry interventions: (1) Low priority; (2) Average priority; (3) High priority; (4) Extreme priority. A final map was made to identify priority areas for landscape recovery in 9 cities located at the mouth of the Mogi Guaçu River Hydrographic Basin, State of São Paulo, Brazil. Considering the natural vulnerability of the land and the multifunctional aspects of the landscape, the scenarios projection allowed a consensus for forest conservation and agricultural suitability perspectives. A final combination of the explored aspects culminated in the spatial indicator, which model foresees 22,300 ha available for urgent actions for restoration, reforestation and sustainable exploitation through agroforestry systems. We emphasize the challenges in reconciling the socioeconomic and ecological functions in the agroecosystem, however, the metric provides a more inclusive and assertive management strategy for natural resources and advances towards the goal of reforestation and implementation of payment for environmental services (PES) schemes.
Keywords: Ecological restoration; Ecosystem services; Forest-based economy; Land use policy – governance; Natural vulnerability; Payments for environmental services